INTERACTIVE MULTIMEDIA THERMODYNAMICS TO IMPROVE CREATIVE THINKING SKILL OF PHYSICS PROSPECTIVE TEACHERS (Department of Physics, Faculty of Mathematics and Natural Sciences, 2017)
This study aims to improve the creative thinking skills of prospective physics teacher as the impact of the application of interactive thermodynamics multimedia (ITMM). The research method used is quasi experiment with control group pretest-posttest design. The subjects consisted of 34 students in the experimental group and 33 students in the control group. Participant students are physics physics semester fourth, in one of the state universities in East Kalimantan. The research instrument consists of multiple choice test items charged with creative thinking skills. Data were analyzed by using difference test of two averages. The normalized gain gain score g of creative thinking skill aspect on the experimental group is 0.60 and the control group is 0.31. This indicates that the creative thinking skills of the prospective physics teacher increase significantly after they experience thermodynamic learning with interactive multimedia. Thus it can be concluded that the use of interactive multimedia improve the creative thinking skills of prospective physics teachers.